Bio-management of root-knot nematode, Meloidogyne incognita - wilt fungus, Fusarium oxysporum disease complex in vegetable cowpea (Indian Journal of Nematology, 2024)
The disease complex caused by Fusarium oxysporum and Meloidogyne incognita is a major threat in vegetable cowpea cultivation. A field study was conducted at the Instructional Farm, Vellayani, to test the effect of different non-chemical methods viz., biofumigation by incorporating cauliflower crop residues, bioagents (Pseudomonas fluorescens, Trichoderma asperellum, Purpureocillium lilacinum) alone and in combination with organic amendment (neem cake, farmyard manure-FYM) in comparison with chemical (fluopyram) for managing the nematode-fungus disease complex in vegetable cowpea. Among the non-chemical methods, seed priming with P. fluorescens (10 g/kg seed) and soil application of neem cake (100 g/m2) showed maximum suppression of nematodes in soil (88.7%) and root (83.8%) over control. Combined application of P. fluorescens (10 g/kg seed) and neem cake (100 g/m2) was as effective as fluopyram 400 SC at 250 g a.i./ha and T. asperellum-enriched FYM at 20 g/m2 in reducing disease incidence and disease index. Regarding growth characters and yield also, the effect of seed treatment with rhizobacteria, P. fluorescens (10 g/kg seed), and neem cake application (100 g/m2) was statistically on par with fluopyram 400 SC at 250 g a.i./ha. The highest number of rhizobial nodules (87 per 5 g root) in plants was recorded in the combination treatment of P. fluorescens and neem cake and it was significantly superior to all other treatments.